Videogames - Newman, James (James A.) (London ; New York : Routledge, 2013)
"James Newman's lucid and engaging introduction guides the reader through the world of videogaming, providing a history of the videogame from its origins in the computer lab to its contemporary status as a global entertainment industry, with characters such as Lara Croft and Sonic the Hedgehog familiar even to those who've never been near a games console. Topics covered include: classifications, game theory and interactivity - what is a videogame? the videogame audience the videogame industry videogame structure narratives and play- approaches to the study of videogames videogames, avatars and virtual worlds social gaming and the culture of videogames This second edition updates the book to include recent developments such as: the popularity of the wii and the increase in non-traditional gamers and more physical gaming the development of MMOGs (massively multiplayer online games) such as World of Warcraft games being downloaded as apps or accessed via mobile phones, iPods and social networking sites"--
Originally published 2004.
Includes bibliographical references and index.
Keywords: Video games; Video games -- Social aspects; GAMES / Video & Electronic; SOCIAL SCIENCE / Media Studies; TECHNOLOGY & ENGINEERING / Social Aspects